In Vitro Regeneration of Dendrobium Through Somatic Embryogenesis from Leaf Explants - Hamiranti, Rahmadyah; Prajaka, Nanang Wahyu; Yeni, Yeni; Maulida, Desi; Erfa, Lisa (International Journal of Applied Sciences and Smart Technologies, 2025)
The purpose of this study was to determine the best basic medium type and TDZ concentration for the development of somatic embryos from Dendrobium orchid leaf explants. Three replications were arranged factorial (2x3) in a completely randomized design for this study. First, there were two types of basic media, ½ MS and MS. The second factor was the concentration of cytokinin thidiazuron 1, 2 and 3 mg/L. Each experimental unit consisted of 5 culture bottles, each contained 5 explants. The research results showed that 1) The use of both types of basic media was able to induce callus formation on Dendrobium 'Gradita 31' orchid from leaf explants. 2) The use of 3 mg/L thidiazuron which combined with ½ MS or MS media was able to form primary callus faster than other treatments. 3) The higher percentage for embryo somatic and shoots formation were also found in 3 mg/L thidiazuron.